Spatial and temporal variation of nitrogen in the medellin river (2010)
Nitrogen is a biogenic element, constituent of organic molecules that play vital functions for any cell [1]. Its origin comes from the mineralization of the organic matter, from the dissolution of sedimentary rocks and from the exchange with the gaseous nitrogen. An increase of organic matter from domestic, agricultural and industrial sources, raises the concentrations of nitrogen, that though it is an essential nutrient, in high concentrations generates harmful effects to the aquatic biota and therefore an ecosystem is unbalanced. In this article an analysis of the spatial variation of the forms of nitrogen: ammonia, nitrites and nitrates in the profile of the river Medellin is done, seeking to understand the phenomena associated with its transformations. In the same way, a temporary analysis from information gathered from the year 1973 of different physicochemical studies made in the river is done. Finally, the growth of population and the uses of the soil with the concentrations of nitrogen are correlated, trying to understand the concentration as a product of the interaction of the man with the nature and the processes of occupation of territory.